2004
DOI: 10.1152/ajprenal.00216.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-α inhibits the repair of oxidative phosphorylation afterS-(1,2-dichlorovinyl)-l-cysteine injury in renal cells

Abstract: Previously, we showed that physiological functions of renal proximal tubular cells (RPTC) do not recover following S-(1,2-dichlorovinyl)-l-cysteine (DCVC)-induced injury. This study investigated the role of protein kinase C-alpha (PKC-alpha) in the lack of repair of mitochondrial function in DCVC-injured RPTC. After DCVC exposure, basal oxygen consumption (Qo(2)), uncoupled Qo(2), oligomycin-sensitive Qo(2), F(1)F(0)-ATPase activity, and ATP production decreased, respectively, to 59, 27, 27, 57, and 68% of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…Here, we demonstrate that human ATPsyn-β is phosphorylated at multiple specific sites in vivo. These results extend our previous work [21] and that of several other studies that have used various phospholabelling techniques or phosphopeptide identification by MS, which have provided indirect evidence for serine/ threonine/tyrosine phosphorylation of ATPsyn-β in yeast, plants and mammalian tissues and cell lines [27][28][29][30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here, we demonstrate that human ATPsyn-β is phosphorylated at multiple specific sites in vivo. These results extend our previous work [21] and that of several other studies that have used various phospholabelling techniques or phosphopeptide identification by MS, which have provided indirect evidence for serine/ threonine/tyrosine phosphorylation of ATPsyn-β in yeast, plants and mammalian tissues and cell lines [27][28][29][30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Consumption of soy proteins, which have been linked to a decreased risk of type 2 diabetes and certain types of cancer, caused decreased phosphorylation of ATPsyn-β and increased ATP synthase activity in the liver of rats [31]. In rat renal cells, PRKCAmediated serine phosphorylation of ATPsyn-β was associated with a decreased ATP synthase activity in vitro [30]. Moreover, in plant mitochondria, the binding of recombinant 14-3-3 protein to phosphorylated serine/threonineresidues on ATPsyn-β inhibited ATP synthase activity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6). As found previously in hPT cells [32][33][34], rPT cells [9,[12][13][14][15][17][18][19][20]26,31], and rabbit proximal tubules [21][22][23][24][25], hPT cells in the current study exhibited decreases in respiration. Modest effects were observed at 10 μM DCVC and none were detected at 1 or 5 μM DCVC.…”
Section: Discussionsupporting
confidence: 86%
“…Changes in mitochondrial Ca 2+ ion homeostasis also appear to be a key step in DCVC-induced renal toxicity [13,[18][19][20]. The importance of mitochondria in DCVC-induced renal toxicity is further highlighted by findings that preservation of mitochondrial function is associated with recovery and repair of epithelial cells from rabbit proximal tubules after sublethal injury from DCVC [21][22][23][24][25]. Other studies in primary cultures of rPT cells, which enable assessment of longer term exposures at lower concentrations as compared to studies that can be conducted in suspensions of freshly isolated cells, showed that DCVC primarily caused necrosis at relatively high concentrations but that concentrations as low as 10 μM increased expression of vimentin [26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using freshly isolated rat proximal tubular cells have indicated that DCVC is a potent cytotoxin, leading to primary mitochondrial dysfunction (Lash et al, 1986a) and inhibition of mitochondrial Ca 2+ sequestration (Vamvakas et al, 1992). The importance of mitochondria in DCVC-induced nephrotoxicity is further highlighted by the studies of rabbit proximal tubules which have demonstrated that the preservation of mitochondrial function is associated with recovery and repair in damaged epithelial cells (Liu et al, 2004;Nowak et al, 1999;Nowak, 2003;Shaik et al, 2007Shaik et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%